Early inter-racial Oneness Pentecostalism : G.T. Haywood and the Pentecostal assemblies of the world (1901-1931) - French, Talmadge L. (Cambridge : James Clarke, 2014)
Early Interracial Oneness Pentecostalism' is a look at what is perhaps the least-known chapter in the history of American Pentecostalism. Th e study of the fi rst thirty years of Oneness Pentecostalism (1901-31) is especially relevant due to its unparalleled interracial commitment to an all- flesh, all-people, counter-cultural Pentecost. This in-depth study details the lives of its earliest primary architects, including G.T. Haywood, R.C. Lawson, J.J. Frazee, and E.W. Doak, and the emergence of Oneness Pentecostalism and its flagship organization, Pentecostal Assemblies of the World. This.
7. The Haywood Era in Oneness Pentecostalism: The Reshaping of Its Legacy and Organizational Context8. Conclusion "Some Day, Some Happy Day!"; Appendix A: Profiles of Early U.S. Oneness Pentecostal Pioneers; Appendix B: Early Oneness Pentecostal Missions (1914-1930); Bibliography; Back cover.
Includes bibliographical references.
CIP data; item not viewed.
Master record variable field(s) change: 650
Keywords: Oneness doctrine (Pentecostalism); Race -- Religious aspects -- Christianity; RELIGION -- Christianity -- Denominations; RELIGION -- Christianity -- Pentecostal & Charismatic; Oneness doctrine (Pentecostalism); Race -- Religious aspects -- Christianity; God -- Simplicity; Oneness Pentecostal churches; Race -- Religious aspects -- Christianity; Oneness doctrine (Pentecostalism); Electronic books